Maximum oxygen consumption (vo2max) in firefighters: systematic review of studies - Rojas Quirós, Jimmy (2013)
Maximum oxygen consumption (VO2max) in firefighters: systematic review of studies. The firefighter’s job is catalogued as a high-risk profession, with high physical requirements; over the last years the firefighter has acquired more competencies other than extinguishing fires; among them interventions in traffic accidents, incidents with hazardous materials, rescues, and forest fires, among others. The traditional image of the fire fighter has given way to new professionals, prepared to face all types of disasters; therefore it is currently referred to as the complete firefighter. The objective of this study was reviewing systematically scientific evidence on the values of maximum oxygen consumption (VO2max) presented by firefighters.  A total of 19 studies were included, published between the years 2002 and 2012, from the databases: EBSCOhost, SpringerLink, SPORTDiscus, Medline, Embase and Scielo; also from journals like: Journal of Sports Science & Medicine, Occupational Medicine and Psicothema. It is conclude by this review, that based on results from the studies, that in the different populations of firefighters, VO2max ranges from 39,20 to 58,21 ml/kg/min.; it varies according to the initial condition the firefighters have on the different studies proposed by the authors; in general it is determined that a firefighter should have VO2max values over 43 ml/kg/min,, which is the minimum recommended, so at least to have a good aerobic capacity, enabling him/her to perform their basic functions as firefighter.